Effect of taper training in collegiate swimmers - Rinehardt, K.; Axtell, R.; Fontana, C.; Breault, R.; Genthe, J.; Garay, R. (Medicine & Science in Sports & Exercise, 2000)
Collegiate female swimmers (N = 13) experienced nine weeks of aerobic overload (8.8% sprint, 34.8% aerobic overload) followed by two weeks of taper training (13.5% sprint, 5.6% aerobic overload). During aerobic overload, the 4 mM anaerobic threshold velocity increased significantly from 1.014 to 1.1.31 m/s. During taper the following measures did not change -- 4mM anaerobic threshold, VO2peak, CK, and LDH. In the dominant shoulder, the following indices did not change -- peak torque, time to peak torque, total work, and average power. Implication. A two-week taper does not alter any measures of aerobic overload training adaptation in female swimmers.